Foraging behavior and honey production of Apismellifera L. - Islam, Md Ektarul; Biswas, Md Jamil Hossain; Ahmed, Kazi Shahanara; Maraj, Faruki Shabia (Asian Journal of Medical and Biological Research, 2015)
Honeybee, Apismellifera L. was reared and maintained in bee box and placed in around Bangladesh Agricultural University campus in Mymensingh to study its life cycle, behaviour, pollen gathering activity, honey production and its effect on yield of mustard. There was no relationship between sunrises, sunset, first out from the box and last entrance into the box. But positive relationship was found with day temperature to first out and last entrance. The highest number of bees collected pollen in the 3rd week of March. Maximum pollen gathering activities were found at 12.00 to 1.00 p.m. The highest amount of honey production was 4.00 kg per box in mustard and there was positive correlation between percent pollen gathering activity and honey production. The highest number of queen cell was found in the month of March. The results showed that honey bee pollination had significant effect on increase in all the plant parameters and yield. Asian J. Med. Biol. Res. June 2015, 1(2): 359-366